Проектування мехатронних систем з заданими вихідними характеристиками - Панченко, Анатолій Іванович; Панченко, Анатолий Иванович; Panchenko, Anatolii; Волошина, Анжела Анатоліївна; Волошина, Анжела Анатольевна; Voloshyna, Anzhela; Панченко, Ігор Анатолійович; Панченко, Игорь Анатольевич; Panchenko, Ihor; Волошин, А. А. (ТДАТУ, 2020)
EN: При проектуванні мехатронних систем, велика увага приділяється забезпеченню заданих вихідних характеристик виконавчих механізмів проектованої системи. Розроблено методику проектування гідравлічних мехатронних систем з елементами багатокритеріальної оптимізації, що дозволяє проектувати мехатронны системи з заданими вихідними характеристиками. Обґрунтовано параметри оптимізації елементів управління мехатронною системою з гідравлічним приводом активних робочих органів самохідної техніки. В результаті проведених досліджень встановлено оптимальні параметри налаштування запобіжного клапана мехатронної системи, що забезпечують відхилення зміни тиску і кутової швидкості виконавчих механізмів від заданих з похибкою 0,17% і 0,67% відповідно. RU: При проектировании мехатронных систем, большое внимание уделяется обеспечению заданных выходных характеристик исполнительных механизмов проектируемой системы. Разработана методика проектирования гидравлических мехатронных систем с элементами многокритериальной оптимизации, позволяющая проектировать мехатронную систему с заданными выходными характеристиками. Обоснованы параметры оптимизации элементов управления мехатронной системой с гидравлическим приводом активных рабочих органов самоходной техники. В результате проведенных исследований установлены оптимальные параметры настройки предохранительного клапана мехатронной системы, обеспечивающие отклонения изменения давления и угловой скорости исполнительных механизмов от заданных с погрешностью 0,17% и 0,67% соответственно. EN: Modern trends to expand the field of application of mechatronic systems with a hydraulic drive of active working bodies of self-propelled vehicles require the development of new approaches to solving the problem of improving the output characteristics of hydraulic drives of mechatronic systems with rotary hydraulic machines. It has been established that orbital and planetary hydraulic motors are most widely used to drive active working bodies and propelled systems of self-propelled vehicles. It should be noted that in previous studies not enough attention was paid to the issues of calculating and designing elements of mechatronic systems with given output characteristics, the proposed mathematical models did not cover all the units of the hydraulic motor and their interconnections, and the introduced number of assumptions to simplify the calculations reduced the accuracy of the obtained indicators. When designing mechatronic systems, much attention is paid to ensuring the specified output characteristics of the actuators of the designed system. A method for designing hydraulic mechatronic systems with elements of multicriteria optimization has been developed, which makes it possible to design a mechatronic system with specified output characteristics. The parameters of optimization of control elements of the mechatronic system with a hydraulic drive of the active working bodies of self-propelled equipment are substantiated. This technique involves five stages: the choice of the parameters of the mechatronic system that affect its output characteristics; justification of the optimized parameters of control elements; development of a model of a mechatronic system with the possibility of optimizing its output characteristics; optimization of the selected parameters of the mechatronic system; analysis of optimization results. The parameters of optimization of control elements of a mechatronic system with a hydraulic drive for active working bodies and propelled systems of self-propelled vehicles are substantiated. As a result of the research, the optimal settings for the mechatronic system safety valve were established, which ensure the deviations of the pressure and angular velocity of the actuators from the specified ones with an error of 0.17% and 0.67%, respectively.
Проектирование мехатронных систем с заданными выходными характеристиками
Design of mechatronic systems with given output characteristics
Keywords: мехатронна система; планетарний гідромотор; вихідні характеристики; критерій оптимізації; інтегрально-квадратична оцінка; мехатронная система; планетарный гидромотор; выходные характеристики; критерий оптимизации; интегрально-квадратичная оценка; planetary hydraulic motor; mechatronic system; output characteristics; optimization criterion; integral quadratic evaluation